The Record Dilemma - Loland, S.
This paper takes a critical look at the origins and characteristics of the concept of sporting records and examines the challenges to sport posed by the continuous quest for new records. First, sport records are defined. Second, the logic of the record is critically examined. It is argued that the continuous quest for new records represents the impossible quest for unlimited growth in (biologically) limited systems. In this way, the quest for records is seen to threaten the very core idea in competitive sport: that it deals primarily with genuine, human performances. Third, then, sport disciplines are categorized according to what is seen as their vulnerability in this respect. Disciplines in which performance depends heavily upon biologically limited basic physical qualities (speed, strength, endurance), and in which technology and tactics play a relatively minor role, are exposed to problematic consequences. Although, logically, new records can be set again and again by finer calibration of measurement technology, the moral and human costs of every improvement will probably increase.